RETRACTED: Solving organizational problems using “X-TRIZ” technique: empirical study - Al-Ali Abdulsattar; Shenshinov Yuri (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001